Access to family resources by families living with schizophrenia: a qualitative study of primary care workers in urban Beijing, China. Issue 9 (7th September 2022) - Wang, Meirong; Chen, Lifen; Tang, Juan; Wei, Yun; Jin, Guanghui; Lu, Xiaoqin
Abstract : Objectives: This study aims to investigate the access to family resources by families living with schizophrenia from the perspective of primary care workers in Beijing, and provide evidence for appropriate and effective family resource coordination in primary care. Design: Qualitative research using individual in-depth interviews to identify the access to family resources by families living with schizophrenia from the perspective of primary care workers. Setting: This study was conducted from September to December 2021 in six urban community health service centres (CHSCs) in Beijing, China. Participants: 3 general practitioners and 10 mental health doctors selected by purposive sampling method from 6 CHSCs in urban Beijing were interviewed. Results: Five themes emerged from the insights of the primary care workers: most family resources are non-targeted for families living with schizophrenia, the publicity of family resources is difficult, burdensome application process of family resources, limited available community-based treatment options and stigma hindering effective communication between families and society. Conclusions: It is necessary to simplify the application process of family resources and provide primary care workers with systematic training regarding family resources. More family resources and improved public attitudes should be promoted for patients with schizophrenia and their caregivers.